INTEGRATING TWO-STAGE UP-FLOW ANAEROBIC SLUDGE BLANKET WITH A SINGLE-STAGE AEROBIC PACKED-BED REACTORFOR RAW PALM OIL MILL EFFLUENT TREATMENT - Khairunnisa Abdul Halim (Water Conservation and Management, 2018)
Annually, enormous amount of palm oil mill effluent (POME) ranging between 56.58 to 70.55 million m3 are producedduring the production of palm oil. Its acidic and high organic loading characteristics can cause severe water pollution if discharged without proper treatment. In Malaysia, most oil palm production mills adopted ponding treatment system. However, this treatment requires high retention time and large build area. Thus, the treatment paradigm has shifted tointegrated high rate bioreactors by coupling anaerobic and aerobic processesdue to the incompetency of the conventional treatment in complying the standard effluent discharged outlined by the Department of Environment.Despite the outstanding treatment performance exhibited by this bioreactor, diluted POME was used in almost all previous studies instead of fresh raw POME. Therefore, the researched bioreactors may not be as efficient in real application. This present study aimed to employ the principle of two-stage anaerobic process followed by a single stage aerobic process for the treatment of fresh raw POME, in whicha two-stage upflow anaerobic sludge blanket digester was integrated with a single-stage anaerobic packed bed reactor. This is to ensure the lignocellulosic components will be broken down into simpler organic compounds in the first stage anaerobic bioreactor followed by their reduction in the second stage anaerobic and single stage aerobic bioreactors.With this, the potential mechanical problems and inhibition on the operational interference of the currently available integrated system is rectified. Thus, the overall performance can be enhanced.The treatment efficiency of this system was examined by evaluating the removal of several important parameters, namely chemical oxygen demand (COD) and sludge reduction reported in terms of total suspended solids (TSS). Throughout the 150 days of operation, approximately 93% and 55% of reduction were observed for COD and TSS, respectively, suggesting this integrated system was competent in treating high strength wastewater.Nonetheless, further research need to be made to ensure the stability consistency and feasibility of this integrated system.